(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Roll drafting is the key part of yarn manufacturing in ring spinning. Because of the fibre length distribution and the accelerated points of fibres in the drafting zone, the drafted strand usually tends to become uneven in terms of its linear density. The reported study mostly focuses on the accelerated points of fibre ends in the drafting zone, and also tries to find out the relation of the changing accelerated points and the irregularity of the drafted yarn. This approach investigates the role of the accelerated points, giving a parabolic-type probabilistic density function to fit the accelerated points of the floating fibres. Therefore, the stochastic simulation of the fibres in the drafting zone is conducted. The simulation process starts from a random fiber bundle nipped by the back roller, and then generates the accelerated point of each fibre by Mont Carlo method. For the given gauge distance and drafting ratio, any strand with a certain fibre length distribution can be simulated in the drafting system. The simulated curve of the number of fibres in the profile of the strand is given with different drafting parameters, which describes the attenuation of the strand in drafting. The results will help us to understand the drafting process and give a method of predicting yarn irregularity from fibre length distribution and drafting parameters.